Sex-Differences and Associations Between Complement Activation and Synovial Vascularization in Patients with Late-Stage Knee Osteoarthritis - Sodhi, Emily U.; Philpott, Holly T.; Carter, McKenzie M.; Birmingham, Trevor B.; Appleton, C. Thomas (Frontiers in Immunology, 2022)
Purpose Synovial inflammation in knee osteoarthritis (OA) causes disorganized synovial angiogenesis and complement activation in synovial fluid, but links between complement and synovial microvascular pathology have not been established. Since complement causes vascular pathology in other diseases and since sex-differences exist in complement activation and in OA, we investigated sex differences in synovial fluid complement factors, synovial tissue vascular pathology, and associations between complement and synovial vascular pathology in patients with late-stage knee OA. Methods Patients with symptomatic, late-stage radiographic knee OA undergoing total knee arthroplasty or high tibial osteotomy provided matched synovial fluid and tissue biopsies during surgery. Complement factors (C2, C5, adipsin, MBL, and CFI) and terminal complement complex (sC5b-C9) were measured in synovial fluid by multiplex or enzyme-linked immunosorbent assay, respectively. Features of synovial vascular pathology (vascularization, perivascular edema, and vasculopathy) were assessed by histopathology. Multivariate linear regression models were used to assess associations between synovial fluid complement factors and histopathological features of vascular pathology, with adjustment for age, sex, body mass index, and sex interaction. Sex-disaggregated comparisons were completed. Results Synovial fluid biomarker and histopathology data were included from 97 patients. Most synovial fluid complement factors and synovial tissue histopathological features were similar between sexes. Synovial fluid C5 trended to lower levels in males (-20.93 ng/mL [95%CI -42.08, 0.23] p=0.05). Median vasculopathy scores (0.42 [95%CI 0.07, 0.77] p=0.02) were higher in males. In the full cohort, C5 concentration was associated with lower vascularization scores (-0.005 [95%CI -0.010, -0.0001] p=0.04) while accounting for sex*C5 interaction. In sex-disaggregated analyses, increased C5 concentration was associated with lower vascularization scores (-0.005 [95%CI –0.009, -0.0001] p=0.04) in male patients, but not in female patients. Males had higher sC5b-C9 compared to females. Additionally, males with high C5 had a higher synovial fluid concentration of sC5b-C9 compared to males with low C5. No differences were found in females. Conclusion Higher synovial fluid C5 levels were associated with increased complement activation and decreased synovial vascularization in males but not in females with OA. Future studies should test whether synovial fluid complement activation suppresses synovial angiogenesis and identify mechanisms accounting for C5-related sex-differences in synovial fluid complement activation in patients with knee OA.